DARI YESUS SEJARAH KE YESUS DIGITAL: MENELUSURI TRANSFORMASI SPIRITUAL DI ERA ARTIFICIAL INTELLIGENCE - Zalukhu, Amirrudin (Lembaga Penelitian STKIP Widya Yuwana, 2025)
The study aims to identify the impact of Jesus AI on individuals' faith and spiritual experiences, as well as the influence of this technology on religious life in the context of growing digital spirituality. The research employs a qualitative approach to explore the transformation of Jesus' role as the center of Christian faith and teachings, as well as a spiritual mediator, from a historical figure in Christian religious tradition to a digital entity introduced by artificial intelligence. Through theological and phenomenological analysis, it examines changes in the representation of Jesus and the evolution of this concept in a society increasingly influenced by technology. A literature review is conducted to analyze theological understandings of Jesus as a historical figure and how this concept has transformed in the digital era. Additionally, observations and analyses of user experiences with Jesus AI (Artificial Intelligence) provide insights into personal interactions with Jesus AI as a spiritual mediator. This approach is expected to offer a comprehensive understanding of the role and influence of Jesus AI in the development of modern spirituality.